Matrix reloaded - Silver, Joel; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Smith, Jada Pinkett, 1971-; Reeves, Keanu; Fishburne, Laurence, III, 1961-; NPV Entertainment (Firm); Silver Pictures; Village Roadshow Pictures; Warner Bros.; Warner Home Video (Firm) ([United States] : Village Roadshow Pictures ; Burbank, CA : Distributed by Warner Home Video, 2010)
Neo, Trinity, and Morpheus continue to lead the revolt against the Machine Army. In their quest to save the human race from extinction, they gain greater insight into the construction of the Matrix and Neo's pivotal role in the fate of mankind.
Special features: written introduction by the Wachowski Brothers; 2 commentaries: Dr. Cornel West and Ken Wilber, Todd McCarthy, John Powers and David Thomson; "Behind the matrix" documentary gallery, 4 featurettes, including "The MTV Movie Awards Reloaded"; "Enter the matrix: the game" documentary; "Enter the matrix: view 23" live-action scenes shot for the video game that plug into the action of "The matrix reloaded"; "Car chase" documentary gallery, 9 featurettes; "Teahouse fight" documentary gallery, 2 featurettes; "Unplugged" documentary gallery, 5 featurettes; "I'll handle them" documentary gallery, 4 featurettes; "The exiles" documentary gallery, 4 featurettes; "P.O.D. sleeping awake" music video; theatrical trailers and tv spots.
Jada Pinkett Smith, Keanu Reeves, Laurence Fishburne.
MPAA rating : R.
MPAA rating: R; sci-fi violence and some sexuality CHV rating: 14A.
Blu-ray disc, 16x9, 2.4:1 presentation; Dolby TrueHD 5.1, Dolby Digital 5.1, Dolby Digital 2.0; 1080p High Definition; requires Blu-ray player.
Subtitled for the deaf and hard of hearing.
Keywords: Computer systems -- Drama; Artificial intelligence -- Drama; Film series; Film sequels; Drama; Feature films; Fiction films; Science fiction films; Video recordings for the hearing impaired